A Natural History of Repetition - Jones, Anne E.; Henzi, S.P.; Barrett, Louise (Journal of Montessori Research, 2019)
The purpose of this study was to understand typically developing children’s repetitive behavior in a free-play, daycare setting. By studying repetition in a non-Montessori setting, we tested the assumption that repetition is a characteristic behavior of all young children and not limited to the Montessori environment. Although Maria Montessori identified repetition during her observations, there is little empirical evidence to support her claim: most research has considered repetition in terms of psychopathology. We collected naturalistic observational data on 31 3- to 6-year-old children for a total of 101 hours to investigate the frequency, contexts, and structure of repetitive bouts. Multilevel model results suggest the ubiquity of repetition, as all children in the study engaged in motor repetition. Furthermore, repetition occurred throughout all free-play activities (construction, animation, fantasy play, rough-and-tumble play, and undirected activity), although repetition was not equally distributed across activities. Motor repetition was not equal across ages either; younger children engaged in more motor repetition than did older children. To understand the structure of repetition, our study also looked at the length of repetition bouts, which ranged from 2 to 19 repetitions and averaged 2.86 repetitions per bout. This natural history of repetition is an influential starting point for understanding the role of repetition in development and is informative to both Montessori and non-Montessori early childhood educators.